PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi pada Perusahaan Manufaktur Sub Sektor Makanan Olahan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2021 - 2025) - Achmad Sulaeman; M. Taufik Azis; Surono (CV. Adiba Aisha Amira, 2026)
This study aims to examine and analyze the effects of Firm Size and Institutional Ownership on Corporate Social Responsibility (CSR) disclosure. The study focuses on manufacturing companies in the processed food subsector listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This research is motivated by the varying levels of CSR disclosure among companies despite the existence of relevant regulations, as well as the empirical inconsistencies found in previous studies. This study employs a quantitative associative approach using secondary data obtained from companies’ annual reports and/or sustainability reports. The research population consisted of 33 companies, and purposive sampling was employed to select 21 companies as the study sample. Following the removal of outliers, a total of 75 valid observations were included in the analysis. CSR disclosure was measured using the Corporate Social Responsibility Disclosure Index (CSRDI), based on 68 indicators from the Global Reporting Initiative (GRI) Standards. The data were analyzed using Panel Data Regression Analysis, with the Random Effects Model (REM) identified as the most appropriate model, using EViews version 13. The partial test results demonstrate that Firm Size has a significant negative effect on CSR disclosure. This finding indicates that larger companies tend to limit their disclosures to regulatory compliance requirements, whereas smaller companies are more proactive in disclosing CSR information to gain social legitimacy. Meanwhile, Institutional Ownership has no significant effect on CSR disclosure. This finding may be attributed to the tendency of institutional investors in Indonesia to prioritize short-term financial returns over corporate sustainability performance. Nevertheless, simultaneously, Firm Size and Institutional Ownership jointly have a significant effect on CSR disclosure.